Pengaruh Sistem Informasi Keuangan Daerah dan Kejelasan Sasaran Anggaran Terhadap Kinerja Organisasi Perangkat Daerah dan Komitmen Organisasi Sebagai Variabel Moderating - Tatian Sartika Marbun; Eka Nurmala Sari; Irfan Irfan (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study aims to test and analyze whether the regional financial information sistem and the clarity of budget targets affect the performance of the Regional Apparatus Organization of the Province of North Sumatra with organizational commitment as the moderator variable. This type of research is using an associative approach. The population in the study were staff employees at the Regional Apparatus Organization of North Sumatra Province. Respondents used are staff employees who fall into the category of Head of Division, Secretary, and Expenditure Treasurer with a total of 99 people. This study consists of independent variables of regional financial information sistems and clarity of budget targets with the dependent variable on performance and organizational commitment as moderating variables. The data analysis technique used in this research is descriptive analysis, analysis of Structural Equation Modeling (SEM) based on variance (Partial Least Square). The results showed that; (1) there is an influence of the regional financial information sistem on OPD performance; (2) there is an effect of clarity of budget targets on the performance accountability of OPD; (3) organizational commitment can moderate the influence of regional financial information systems on OPD performance; (4) organizational commitment can moderate the effect of clarity of budget targets on OPD performance